2019
DOI: 10.1636/0161-8202-47.3.344
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism and patterns of sexual behavior in Lustrochernes argentinus (Pseudoscorpiones: Chernetidae)

Abstract: Sexual dimorphism between females and males can sometimes be related to particular mating behaviors. In pseudoscorpions, very little is known about the relationship between sexual size dimorphism (SSD) and reproductive behavior. This paper describes sexual dimorphism and the mating behavior patterns of Lustrochernes argentinus (Thorell, 1877), a Neotropical species of Cheliferoidea. We measured different body structures and appendages of 14 individuals of each sex, with the values compared with a T-test. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The term ''behavioral unit'' was used, similarly to other recent publications (Stanley et al 2016;Palen-Pietri et al 2019) on arachnid mating behavior. Major behavioral units were named according to existing terms from Weygoldt (1969); the terminology of genital structures follows Legg (1974a, b).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The term ''behavioral unit'' was used, similarly to other recent publications (Stanley et al 2016;Palen-Pietri et al 2019) on arachnid mating behavior. Major behavioral units were named according to existing terms from Weygoldt (1969); the terminology of genital structures follows Legg (1974a, b).…”
Section: Methodsmentioning
confidence: 99%
“…In the past decades, publications on mating behavior of pseudoscorpions were almost exclusively dedicated to species of the cheliferoid family Chernetidae (Zeh & Zeh 1992, 1997Andrade & Gnaspini 2003;Palen-Pietri et al 2019), whereas mating in Cheliferidae has not been studied recently. Quantitative studies on mating, as already available for some other arachnid groups (e.g., Girard et al 2011;Fowler-Finn et al 2019), are scarce for pseudoscorpions (Palen-Pietri et al 2019) and particularly missing in Cheliferidae.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Videos were analyzed using JWatcher software (Blumstein & Daniel, 2007) to identify the main behaviors. The variables considered were: (1) rejection by female (the female permanently interrupts pedipalp grasping when the male is depositing the spermatophore), (2) rejection by male (the male permanently interrupts contact with the female after briefly grasping her pedipalps during phase I), and (3) occurrence of sperm uptake (the female presses her genital opening over the spermatophore taking the sperm packet); the emptied spermatophore is easily distinguishable (Palen-Pietri et al, 2019).…”
Section: Effect Of Gregarines On Matingmentioning
confidence: 99%
“…A species where intersexual contact exists during mating is Lustrochernes argentinus (Thorell), a neotropical pseudoscorpion that belongs to the Chernetidae family. The courtship of this species has a duration of approximately 7 min, and it is divided into three phases: (i) examination (2 min), where individuals assess their potential partner while grasping each other's pedipalps, (ii) spermatophore deposition (5 min), where stimulation behaviors such as rubbing chelicera occur, and (iii) sperm transfer (10 s), where the female actively performs the sperm uptake from the fresh spermatophore (Palen‐Pietri et al, 2019). During the analysis of L. argentinus , we observed that, in some cases, both males and females could choose not to mate with the individual present in the arena suggesting mutual mate choice.…”
Section: Introductionmentioning
confidence: 99%